La Fattoria Medicea di Cascine di Tavola a Prato Un Progetto Integrato di Territorio per la rigenerazione patrimoniale di un paesaggio vivente - CENTAURO, GIUSEPPE ALBERTO (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
The Medici's Farm of Cascine di Tavola, commissioned by Lorenzo Il Magnifico in 1477, and the set of agro-environmental areas functional to it, have over time been configured as an extraordinary unitary system of agro-environmental and cultural-landscape value and of exemplary relevance as a model of co-evolutionary man-nature management of the territory. Starting from this legacy - and also from the improper management and interventions of which it was subject in the second half of the nineteenth century - the research seeks to retain the genealogy and identity of this heritage, identifying, both in terms of analysis and design scenario, the conditions for a realistic process of regeneration not only of the cultural heritage that characterizes it but also of its territorial "framing" function and as a tool for "socio-ecological" innovation and sustainable local planning and development.